Effect of number of associated anomalies on outcome in oesophageal atresia with or without tracheoesophageal fistula patient - Amit Singh; Minu Bajpai; V Bhatnagar; Sandeep Agarwala; M Srinivas; Nitin Sharma (Wolters Kluwer Medknow Publications, 2013)
Background: The objective of this study was to assess effect of number of associated anomalies on outcome in oesophageal atresia with or without tracheoesophageal fistula patients. Materials and Methods: Retrospective analysis of records of neonates admitted with a diagnosis of oesophageal atresia (EA) with or without tracheoesophageal fistula during January 2005 to May 2011. Preoperative investigation included chest X-Ray, ultrasonography of abdomen and echocardiography. Associated anomalies were grouped as minor or major depending on whether life threatening or not. Major anomalies were further sub grouped according to the involvement of single, two or > 2 organ systems. Survival was correlated with the presence of anomalies and the number of systems involved. Results: Out of 301 patients with EA, 240 survived (79.7%). Of these 301, 117 (38.9%) had no associated anomalies. Of the total 61 deaths, 59% (36/61) were in patients with cardiac anomalies and 44% (27/61) were in those with >2 associated anomalies. The mortality rate was highest in those with >2 anomalies 27/34 (79.4%), whereas survival was best in those without any associated anomalies 104/117 (88.9%). Conclusions: Apart from other factors, an association of more than two system anomalies influence the mortality in oesophageal atresia.